A construção da identidade feminina em Duas Iguais, de Cíntia Moscovich - Matté, Manuela (My University, 2015)
The subject of this dissertation consists of analyzing the female identity and subjectivity construction of the character Clara, protagonist-narrator of the novel Duas iguais, by Cíntia Moscovich. Therefore, it is observed how the process of identity affirmation of the female subject represented in the novel occurs, considering the social, historical and cultural context in which this subject is inserted: a Jewish regional community, during Brazilian military dictatorship years (1964-1985). Aspects regarding memory, cultural region, Judaism, patriarchy, homosexuality, prejudice, love, subjectivity and identity are discussed. Gender studies and feminist critics, studies about culture, identity and regionality are used as theoretical support for this work.
O tema da presente dissertação consiste na análise da construção da identidade e da subjetividade femininas da personagem Clara, narradora-protagonista da obra Duas iguais, de Cíntia Moscovich. Nesse sentido, observa-se como ocorre o processo de afirmação identitária do sujeito feminino representado na obra, considerando-se o contexto sócio-histórico-cultural em que está inserido: uma comunidade regional judaica, à época da ditadura militar brasileira (1964-1985). Para tanto, são discutidos aspectos como memória, região cultural, judaísmo, patriarcalismo, homossexualidade, preconceito, amor, subjetividade e identidade. Servem como aporte teórico a este trabalho os estudos culturais de gênero e a crítica literária feminista, bem como estudos acerca de cultura, identidade e regionalidade.
Keywords: Moscovich, Cíntia, 1958-; Literatura brasileira - Ficção - Crítica e interpretação; Mulheres na literatura; Personalidade; Subjetividade; Brazilian literature - Fiction - Criticism and interpretation; Women in literature; Personality; Subjectivity